Steady-State Radial Flow Modeling through the Production Well in the Confined Aquifer of Monzoungoudo, Benin - Codo, Francois de Paule; HOUNTONDJI, Babilas; AÏNA, MARTIN PÉPIN (My University, 2019)
This study aims to develop a mathematical analysis for one-dimensional modeling of a radial flow through a production well drilled in a confined aquifer, in the case of steady-state flow conditions. An analytical solution has derived from that expression for estimation of drawdowns according to different flowrates. Through that process, the evaluation of static pressure, the calculation of hydraulic charge due to the waterflow through the well is evaluated, the drawdowns curves are drawn and at last, the obtained curves are analyzed. The curves obtained for the different flow rates have an asymptotic direction, the axis of the hydraulic charges. The variation of the hydraulic charge depends on the radial distance for different flow rates. The P point, is a common point of all curves obtained for different production flowrates in the well. This point is where the well production flowrate is optimum for the optimal hydraulic charge.
Keywords: Confined Aquifer; Production Well; Radial Flow; Steady-State Flow; Drawdown; Cone of Depression